Computer-assisted pronunciation and intonation learning systems for foreign language instructioin - Y. A. Zdaranok (Цифровая трансформация)
This article describes computer systems for teaching pronunciation and intonation which are designed specifically to evaluate and improve pronunciation while learning a foreign language. The evaluation of developed computer programs that can supplement the learning process in a classroom and provide unique prerequisites for mastering a non-native language is given: overcoming the language barrier, reducing anxiety, accessibility and individual training program. Positive factors of computer systems for learning pronunciation and intonation are noted, which support the system data with detailed and corrective forms of feedback while still meeting all the requirements of the system. The regularity of the fact that the training of a prosody of a foreign language requires a palette of intonation contours to convey the whole variety of thoughts in speech. Therefore, intonation should be studied in the context of well-structured dialogues or discourse.